2023
DOI: 10.1186/s40643-023-00671-2
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue by porous biochar obtained by KOH activation from bamboo biochar

Abstract: A series of activated biochar (KBBC-700, KBBC-800 and KBBC-900) which were modified by KOH and pyrolysis at various temperatures from ball-milling bamboo powder were obtained. The physicochemical properties and pore structures of activated biochar were investigated by scanning electron microscopy (SEM), fourier transform infrared spectoscopy (FT-IR), X-ray diffraction (XRD) and N2 adsorption/desorption. The adsorption performance for the removal of methylene blue (MB) was deeply studied. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…KOH promoted the formation of mesoporosity in the biochar. This is confirmed by research [ 100 ] that confirms the increased adsorption of MB on KOH-modified biochar. However, Samaraweera et al, 2023 [ 101 ] indicate that Douglas fir biochar modified with Fe 3 O 4 showed a higher sorption capacity than raw biochar.…”
Section: Resultssupporting
confidence: 81%
“…KOH promoted the formation of mesoporosity in the biochar. This is confirmed by research [ 100 ] that confirms the increased adsorption of MB on KOH-modified biochar. However, Samaraweera et al, 2023 [ 101 ] indicate that Douglas fir biochar modified with Fe 3 O 4 showed a higher sorption capacity than raw biochar.…”
Section: Resultssupporting
confidence: 81%
“…This behavior predominantly arises from a synergy between physical and chemical adsorption mechanisms (Bhattacharyya et al, 2018). The rise in temperature increased the number of active sites on the Femodified biochar as well as its porosity and overall pore volume, which improved the surface's ability to bind antibiotics and, as a result, enhanced the adsorption process (Ge et al, 2023). In most studies, as the temperature rises, the solubility of antibiotics tends to decrease, consequently leading to an increase in adsorption (Aoulad et al, 2023).…”
Section: Effect Of Temperature On the Removal Of Antibioticsmentioning
confidence: 99%
“…However, these lignocellulosic biomasses can be pyrolyzed to produce higher-value products like biochar for efficient removal of organic pollutants such as textile dyes from wastewater. The removal of textile dyes, including Methylene Blue [ 17 , 18 ], Remazol Brilliant Blue (RBB) [ 19 , 20 ], and Congo Red [ 21 , 22 ] (CR) from wastewater are efficiently achieved through biochar. Biochar, derived from organic waste, acts as an effective adsorbent, capturing and immobilizing dye molecules in its porous structure.…”
Section: Introductionmentioning
confidence: 99%